2015
DOI: 10.1177/0284185114529562
|View full text |Cite
|
Sign up to set email alerts
|

Bosniak classification system: inter-observer and intra-observer agreement among experienced uroradiologists

Abstract: According to the calculated weighted κ all readers performed "very good" for both inter-observer and intra-observer variation. Most variation was seen in cysts catagorized as Bosniak II, IIF, and III. These results show that radiologists who evaluate complex renal cysts routinely may apply the Bosniak classification reproducibly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
2
22
1
1
Order By: Relevance
“…Bosniak version 2019 had a higher diagnostic specificity for malignancy than did The interobserver agreement in version 2019 was superior to that in previous studies (k = 0.51-0.52) based on MRI (16) or CT (17) scans, probably because of more objective and precise classification criteria. However, agreement was lower than that of other previous studies (k = 0.66-0.85) (10,(18)(19)(20), partially because of the relatively small number of malignant tumors, fewer readers, higher rate of class I and IV CRMs, or the bias in the inclusion of CRMs and establishment of the study cohort in those studies.…”
Section: Comparison Of Interobserver Agreement Between Version 2019 Acontrasting
confidence: 76%
“…Bosniak version 2019 had a higher diagnostic specificity for malignancy than did The interobserver agreement in version 2019 was superior to that in previous studies (k = 0.51-0.52) based on MRI (16) or CT (17) scans, probably because of more objective and precise classification criteria. However, agreement was lower than that of other previous studies (k = 0.66-0.85) (10,(18)(19)(20), partially because of the relatively small number of malignant tumors, fewer readers, higher rate of class I and IV CRMs, or the bias in the inclusion of CRMs and establishment of the study cohort in those studies.…”
Section: Comparison Of Interobserver Agreement Between Version 2019 Acontrasting
confidence: 76%
“…It is probable that most urologists in tertiary centres tend to manage these patients similarly, but this guide can be used by primacy care or office urologists to counsel their patients appropriately. The major known drawback of the BCS is the substantial inter- and intra-observer variation, specifically in the Bosniak IIF and III categories [2] , [3] , [4] . The confidence in agreement is also experience dependent: ‘The more skilled radiologist the less decrease in confidence with regard to CT or MRI’ [4] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The Bosniak classification system (BCS) for cystic renal lesions was developed based on CT findings [1] . The BCS is reader dependent and prone to inter- and intra-reader variations [2] , [3] , [4] . Israel et al [5] showed that the BCS in CT and MRI are similar in most cystic renal lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on imaging findings, this child's never‐biopsied multiple septated renal cysts are highly likely to be CN, a lesion classically associated with DICER1 mutations . CN usually presents as unilateral single or multiple septated cysts . In DICER1 syndrome, CN develops almost exclusively between birth and age of 4 years …”
Section: Discussionmentioning
confidence: 99%
“…[3,6] CN usually presents as unilateral single or multiple septated cysts. [7] In DICER1 syndrome, CN develops almost exclusively between birth and age of 4 years. [4,6] ASK in carriers of DICER1 mutations appears to represent neoplastic transformation of CN (Fig.…”
Section: Discussionmentioning
confidence: 99%